Zonas climáticas locais em cidades pequenas: relação entre temperatura e morfologia urbana - Castro, Lidia Gomes de (2022)
The urban growth and population densification dynamics causes socio-environmental effects, especially in absence sustainable planning adequate, chiefly in equatorial regions, where the formation of Urban Heat Islands (UHI) carries negative effects on the thermal population comfort. Remote sensing enables the identification of warmer areas superficially due to the radiation emitted by the bodies arranged in the studied environment, linked to this, the morphological characterization contributes to the identification of the thermal changes causes. In summary, this research aims to highlight what are the effects on the thermal dynamics of a small city with equatorial sub-humid climate as Eusebio (CE) in the midst of the urban morphological modification process, from the relation analysis between three variables: Local Climate Zones (LCZ), Surface Temperature (LST) and Air Temperature (AT). In brief, the ZCL was used as methodology to Eusebio's urban morphological landscape classification, based on height, roughness, coverage and thermal admission of materials (STEWART AND OKE, 2012); for characterization of the surface thermal dynamics, TST maps and graphs were prepared from the thermal infrared bands of Landsat 5 and 8 satellites for a temporal analysis (2001 to 2021); and two Mobile Transects were performed in the 2021’s dry period with AT at 125 points in the municipality incorporating areas with different morphologies. The remote sensing geoprocessing operations was developed from the open source platform Google Earth Engine (GEE) and the software ARCGIS 10.5, followed by descriptive and inferential statistical analysis. In the 2001's median data sample, the LST is in the 25 °C range and has lower values that come close to 20 °C, while for 2021's median is above 30 °C. In the thermal maps, it is possible to see that urban features have replaced green areas over the years. At 6 PM, the air temperature measurements registered a range of 27.50 °C to 28.90 °C, with the highest values concentrated in the Cidade Alpha and Tamatanduba neighborhoods. The main influences on TA are by the construction type, anthropogenic flow and ground cover type, an association observed in the analysis of the 2021's LST, in the identified LCZ classes and in the mobile transects, evidencing areas related to water and vegetation suppression in detriment of urbanization.